The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/nano8100770
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPV1 Channel Activity in Human CD4+ T Cells by Nanodiamond and Nanoplatinum Liquid, DPV576

Abstract: Background: Transient receptor potential vanilloid (TRPV) channels act as sensors of pain, temperature, and other external stimuli. We have recently shown that DPV576, an aqueous mixture of nanodiamond (ND) and nanoplatinum (NP), can modulate the activity of TRPV on human primary keratinocytes, suggesting their potential as a possible pain modulator. Here, we sought to examine the effect of DPV576 in modulating the functions of human CD4+ T lymphocytes and whether the modulation is mediated via TRPV channels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In addition, DPV576 (a dispersed aqueous mixture composed of nanodiamond and nanoplatinum) activates human DCs and upregulates the levels of DC-secreted cytokine IL-10, 33 and we have recently observed that exposure of human CD4+ T lymphocytes to DPV576 inhibits the activity of the transient receptor potential vanilloid channel TRPV1 in CD4+ T lymphocytes, suggesting that it has the potential for use in pain management. 34 Work of others on the anti-inflammatory activity of several natural agents has also shown effects on IL-10 and DCs. Lippia sidoides , an aromatic shrub, can induce IL-10 production in THP-1 monocytes; 35 PureCell Complex (PCT)-233, an active molecular complex from Spinacia oleracea , increased IL-10 production but did not significantly modulate TNF release in alveolar macrophages treated with PCT-233 and budesonide after LPS stimulation; 36 and a complex mixture of herbal extracts has been shown to modulate the innate responsiveness of murine DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DPV576 (a dispersed aqueous mixture composed of nanodiamond and nanoplatinum) activates human DCs and upregulates the levels of DC-secreted cytokine IL-10, 33 and we have recently observed that exposure of human CD4+ T lymphocytes to DPV576 inhibits the activity of the transient receptor potential vanilloid channel TRPV1 in CD4+ T lymphocytes, suggesting that it has the potential for use in pain management. 34 Work of others on the anti-inflammatory activity of several natural agents has also shown effects on IL-10 and DCs. Lippia sidoides , an aromatic shrub, can induce IL-10 production in THP-1 monocytes; 35 PureCell Complex (PCT)-233, an active molecular complex from Spinacia oleracea , increased IL-10 production but did not significantly modulate TNF release in alveolar macrophages treated with PCT-233 and budesonide after LPS stimulation; 36 and a complex mixture of herbal extracts has been shown to modulate the innate responsiveness of murine DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In a sepsis model, the LPS-stimulated peritoneal macrophages showed an impaired phagocytosis when TRPV1 was knockout (36), suggesting the putative role of TRPV1 to potentiate macrophages. In CD4 + T cells, TRPV1 was associated with T cell receptor (TCR) and facilitated TCR-induced Ca 2+ inflow (37), and the activity of CD4 + T cells was impaired via the inhibition of TRPV1 (38). The activation of TRPV1 was also reported to enhance leukocyte rolling and adhesion (39).…”
Section: Trp Channels In Immune Cellsmentioning
confidence: 99%
“…TRPV1 has been associated with T cell antigen receptor-induced calcium influx and signaling as well as non-canonical (MHC-independent) T cell activation in a mouse colitis model, in which it promotes T cell responses to increase intestinal inflammation [174]. Treatment of activated CD4 + T cells with DPV576 (an aqueous mixture of nanodiamond and nanoplatinum) resulted in specifically decreased expression of TRPV1 [394]. Ghoneum et al showed that this downregulation was accompanied by decreased IFN-γ secretion in capsaicin-activated CD4 + T cells [394].…”
Section: Sex Hormones and Other Specific Examples: Trpv1mentioning
confidence: 99%
“…Treatment of activated CD4 + T cells with DPV576 (an aqueous mixture of nanodiamond and nanoplatinum) resulted in specifically decreased expression of TRPV1 [394]. Ghoneum et al showed that this downregulation was accompanied by decreased IFN-γ secretion in capsaicin-activated CD4 + T cells [394]. T cells interact with macrophages and neutrophils, with these innate immune cells releasing cytokines that in turn modulate TRPV1 and TRPA1 [395,396].…”
Section: Sex Hormones and Other Specific Examples: Trpv1mentioning
confidence: 99%